2021
DOI: 10.1007/s40996-021-00777-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Thermal Stimulation of Superplasticizers on Fresh Properties of Cement Mortar

Abstract: Polycarboxylic acid-based superplasticizers are used in various types of concrete work. Wide variations in environmental temperatures are known to affect how well chemical admixtures perform as superplasticizers, influencing the properties of the concrete. However, little has been reported on changes in performance caused by thermal variations. Previous studies have reported that heating superplasticizers change the polymer structure, improving and sustaining cement particles' dispersibility. Moreover, the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The amount of superplasticizer added was set so that the value of 0 tamp flow without thermal stimulation was 120 ± 10 mm for each formulation. In Case 1, the dispersion performance was different between LSC and MSN, and the sand to cement ratio (S/C) could not secure the prescribed fluidity under the same conditions as in the previous studies [15,16,17]. Therefore, by setting the S/C to 1.5, it was possible to confirm the fluidity improvement due to thermal stimulation of the in this study.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…The amount of superplasticizer added was set so that the value of 0 tamp flow without thermal stimulation was 120 ± 10 mm for each formulation. In Case 1, the dispersion performance was different between LSC and MSN, and the sand to cement ratio (S/C) could not secure the prescribed fluidity under the same conditions as in the previous studies [15,16,17]. Therefore, by setting the S/C to 1.5, it was possible to confirm the fluidity improvement due to thermal stimulation of the in this study.…”
Section: Introductionmentioning
confidence: 60%
“…In our various studies [15,16,17] to verify that when a superplasticizer is stimulated by heat (hereafter, referred to as "thermal stimulation"), the polymer molecule's stereoscopic projection area in the superplasticizer changes, and the region that adsorbs cement particles expands. Based on the results, it was confirmed that the fluidity and construction performance was improved by thermal stimulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation